2014
DOI: 10.1016/j.anifeedsci.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Bioflavex® and its pure flavonoid components on in vitro fermentation parameters and methane production in rumen fluid from steers given high concentrate diets

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 4.0 de Creative Commons The effect of Bioflavex ® and its pure flavonoid components on in vitro fermentation parameters and methane production in rumen fluid from steers given high concentrate diets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
92
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 32 publications
11
92
1
3
Order By: Relevance
“…Our results strongly suggest that flavonoids contribute the most to reducing CH 4 production and it may be particularly useful for a general screening for plants possessing antimethanogenic activity. Otherwise, TF and CT fractions are both associated with a lower CH 4 emission, however, the mechanisms through which they decrease CH 4 appear to differ.This supports previous studies which reported that ruminal CH 4 production may be lower when using diets containing flavonoids (Garcıa-Gonzalez et al, 2008a b; Balcells et al, 2012;Oskoueian et al, 2013 ;Seradj et al, 2014). But this is not always the case (Broudiscou et al, 2000(Broudiscou et al, , 2002.…”
Section: Ruminal Fermentation Parameterssupporting
confidence: 78%
“…Our results strongly suggest that flavonoids contribute the most to reducing CH 4 production and it may be particularly useful for a general screening for plants possessing antimethanogenic activity. Otherwise, TF and CT fractions are both associated with a lower CH 4 emission, however, the mechanisms through which they decrease CH 4 appear to differ.This supports previous studies which reported that ruminal CH 4 production may be lower when using diets containing flavonoids (Garcıa-Gonzalez et al, 2008a b; Balcells et al, 2012;Oskoueian et al, 2013 ;Seradj et al, 2014). But this is not always the case (Broudiscou et al, 2000(Broudiscou et al, , 2002.…”
Section: Ruminal Fermentation Parameterssupporting
confidence: 78%
“…Various phytochemicals have been shown to modulate rumen fermentation favourably, and to inhibit methane production in the rumen Saxena, 2010, 2011;Seradj et al, 2014). Tree leaves, which contain tannins and saponins in varying amounts, may be incorporated in diets to mitigate enteric methane emissions (Patra and Saxena, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we investigated the effect of supplementation of resveratrol on in vitro methane production, rumen fermentation and prokaryotic communities using the 16S rRNA sequencing method under two different diets (forage‐based and concentrate‐based) and two time points (12 and 24 h) that reflect the types of diet of fattening lambs and feeding regimens in practice respectively. In vitro fermentation techniques involve the incubation of substrates (usually the diets) with a rumen fluid, which have been widely used to evaluate the effect of polyphenols such as tannins (Jayanegara et al , 2015; Witzig et al , 2018) and flavonoids (Oskoueian et al , 2013; Seradj et al , 2014) on VFA production and methane production. Although the results obtained from in vitro fermentation techniques cannot completely reflect or replace those obtained from in vivo studies (Benchaar et al , 2008; Oh and Hristov, 2016), they offer a rapid and less expensive alternative to evaluate nutrient utilization in vivo (Rymer et al , 2005).…”
Section: Introductionmentioning
confidence: 99%